Prediction of individualized lifetime benefit from cholesterol lowering, blood pressure lowering, antithrombotic therapy, and smoking cessation in apparently healthy people. (18th May 2019) - Jaspers, Nicole E M; Blaha, Michael J; Matsushita, Kunihiro; van der Schouw, Yvonne T; Wareham, Nicholas J; Khaw, Kay-Tee; Geisel, Marie H; Lehmann, Nils; Erbel, Raimund; Jöckel, Karl-Heinz; van der Graaf, Yolanda; Verschuren, W M Monique; et al.
Abstract: Aims: The benefit an individual can expect from preventive therapy varies based on risk-factor burden, competing risks, and treatment duration. We developed and validated the LIFEtime-perspective CardioVascular Disease (LIFE-CVD) model for the estimation of individual-level 10 years and lifetime treatment-effects of cholesterol lowering, blood pressure lowering, antithrombotic therapy, and smoking cessation in apparently healthy people. Methods and results: Model development was conducted in the Multi-Ethnic Study of Atherosclerosis ( n  = 6715) using clinical predictors. The model consists of two complementary Fine and Gray competing-risk adjusted left-truncated subdistribution hazard functions: one for hard cardiovascular disease (CVD)-events, and one for non-CVD mortality. Therapy-effects were estimated by combining the functions with hazard ratios from preventive therapy trials. External validation was performed in the Atherosclerosis Risk in Communities ( n  = 9250), Heinz Nixdorf Recall ( n  = 4177), and the European Prospective Investigation into Cancer and Nutrition-Netherlands ( n  = 25 833), and Norfolk ( n  = 23 548) studies. Calibration of the LIFE-CVD model was good and c-statistics were 0.67–0.76. The output enables the comparison of short-term vs. long-term therapy-benefit. In two people aged 45 and 70 with otherwise identical risk-factors, the older patient has a greater 10-year absolute risk reduction (11.3% vs. 1.0%) but a smaller gain in life-years free of CVD (3.4 vs. 4.5 years) from the same therapy. The model was developed into an interactive online calculator available via www.U-Prevent.com . Conclusion: The model can accurately estimate individual-level prognosis and treatment-effects in terms of improved 10-year risk, lifetime risk, and life-expectancy free of CVD. The model is easily accessible and can be used to facilitate personalized-medicine and doctor–patient communication.